Labor markets in Latin America : combining social protection with market flexibility - Edwards, Sebastian, 1953-; Lustig, Nora (Brookings Institution Press, 1997)
Many of the rules that govern labor markets in Latin America (and elsewhere) raise labor costs, create barriers to entry, and introduce rigidities in the employment structure. These include the exceedingly restrictive regulations on hiring and firing practices, as well as burdensome social insurance schemes. Such labor market regulations contribute to an over-expansion of precarious forms of employment and to rural poverty, and hinder countries from responding rapidly to new challenges from increased foreign competition. At the same time, other norms can reduce costs and raise productivity; th.